Resting heart rate: Its correlations and potential for screening metabolic dysfunctions in adolescents - Fernandes, Rômulo A. [UNESP]; Vaz Ronque, Enio R.; Venturini, Danielle; Barbosa, Décio S.; Silva, Danilo P.; Cogo, Crisieli T.; Carnelossi, Mariana Souza; Batista, Mariana B.; Coelho-e-Silva, Manuel J.; Sardinha, Luís B.; Cyrino, Edilson S. (Springer Nature, 2013)
Background: In pediatric populations, the use of resting heart rate as a health index remains unclear, mainly in epidemiological settings. The aims of this study were to analyze the impact of resting heart rate on screening dyslipidemia and high blood glucose and also to identify its significance in pediatric populations.Methods: The sample was composed of 971 randomly selected adolescents aged 11 to 17 years (410 boys and 561 girls). Resting heart rate was measured with oscillometric devices using two types of cuffs according to the arm circumference. Biochemical parameters triglycerides, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol and glucose were measured. Body fatness, sleep, smoking, alcohol consumption and cardiorespiratory fitness were analyzed.Results: Resting heart rate was positively related to higher sleep quality (β = 0.005, p = 0.039) and negatively related to cardiorespiratory fitness (β = -0.207, p = 0.001). The receiver operating characteristic curve indicated significant potential for resting heart rate in the screening of adolescents at increased values of fasting glucose (area under curve = 0.611 ± 0.039 [0.534 - 0.688]) and triglycerides (area under curve = 0.618 ± 0.044 [0.531 - 0.705]).Conclusion: High resting heart rate constitutes a significant and independent risk related to dyslipidemia and high blood glucose in pediatric populations. Sleep and cardiorespiratory fitness are two important determinants of the resting heart rate. © 2013 Fernandes et al.; licensee BioMed Central Ltd.
Keywords: Adipose tissue; Adolescent; Glucose; Heart rate; Lipid; Physical fitness; Sleep; alcohol; cholesterol; glucose; high density lipoprotein cholesterol; low density lipoprotein cholesterol; triacylglycerol; adolescent; alcohol consumption; blood chemistry; blood sampling; body fat; cardiorespiratory fitness; child; cholesterol blood level; controlled study; cuff; diagnostic test accuracy study; diet restriction; dyslipidemia; female; fitness; glucose blood level; human; hyperglycemia; major clinical study; male; metabolic disorder; oscillometry; pediatrics; receiver operating characteristic; resting heart rate; school child; screening test; sensitivity and specificity; sleep; sleep quality; smoking; triacylglycerol blood level